2021
DOI: 10.1101/2021.01.15.426899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep problems in preschoolers with autism spectrum disorders are associated with sensory sensitivities and thalamocortical overconnectivity

Abstract: Projections between the thalamus and sensory cortices are established early in development and play an important role in sleep regulation as well as in relaying sensory information to cortex. Atypical thalamocortical functional connectivity frequently observed in children with autism spectrum disorders (ASD) might therefore be linked to sensory and sleep problems common in ASD. Here we investigated the relationship between auditory-thalamic functional connectivity measured during natural sleep fMRI, sleep prob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Less positively, studies have also reported that autistic people with sensory reactivity are more likely to experience sleep problems (Dwyer et al, 2022;Han et al, 2022;Linke et al, 2021), and hyper-reactivity to sensory input may predict sleep difficulties later in life (Manelis-Baram et al, 2022;Mazurek et al, 2019). Although prior studies have yielded inconsistent outcomes with respect to those sensory modalities most critical for exacerbating sleep problems (Linke et al, 2021;Manelis-Baram et al, 2022;Tzischinsky et al, 2018), it appears that auditory filtering is a contributing factor (Hollway et al, 2013;Wang et al, 2019). Sleep problems can, in turn, negatively impact autistic people's ability to navigate the world, leading to diminished quality of life (Deserno et al, 2019;Lin & Huang, 2019;McLean et al, 2021).…”
Section: Auditory Processing and Non-social Traitsmentioning
confidence: 99%
“…Less positively, studies have also reported that autistic people with sensory reactivity are more likely to experience sleep problems (Dwyer et al, 2022;Han et al, 2022;Linke et al, 2021), and hyper-reactivity to sensory input may predict sleep difficulties later in life (Manelis-Baram et al, 2022;Mazurek et al, 2019). Although prior studies have yielded inconsistent outcomes with respect to those sensory modalities most critical for exacerbating sleep problems (Linke et al, 2021;Manelis-Baram et al, 2022;Tzischinsky et al, 2018), it appears that auditory filtering is a contributing factor (Hollway et al, 2013;Wang et al, 2019). Sleep problems can, in turn, negatively impact autistic people's ability to navigate the world, leading to diminished quality of life (Deserno et al, 2019;Lin & Huang, 2019;McLean et al, 2021).…”
Section: Auditory Processing and Non-social Traitsmentioning
confidence: 99%